The Double Transverse Microvascular Clamp: A New Instrument for Microsurgical Anastomoses - El-Shazly, Mohamed (Journal of Reconstructive Microsurgery, 2012)
Since the introduction of microvascular surgeries, the sophisticated ideas and techniques of tissue transplantations are continually advancing and searching for the best work conditions to present the best outcomes in these critical interferences. Every tissue transplant has its donor vessels, artery and vein, which should be anastomosed to recipient vessels. A new instrument, the double transverse microvascular clamp (DTMC), has been developed to be applied simultaneously, as one clamp, to both the artery and its accompanying vein. The transverse design of this clamp keeps the artery separate from its vein, allowing each anastomosis to be performed more easily. The limited clamp surface area minimizes the glazing and blurring effects. Applying only one clamp to the two vessels presents more work space and overcomes the crowdedness caused by the use of two single clamps. Using a DTMC on both the recipient and donor vessels provides optimal suture maneuverability and ideal work situation compared with the use of two double approximating clamps. We believe this DTMC would be a valuable addition to the microsurgical instruments market.
Keywords: clamp; microvascular; anastomoses